Theoretical triangulation and pluralism in research methods in organizational and accounting research - Hoque, Z.; Covaleski, M. A.; Gooneratne, T.N. (Emerald Publishing, 2013)
Purpose – The purpose of this paper is to present a critical review of the contributions of multiple theories to accounting and organizational research, which is often referred to as “theoretical triangulation” or “theoretical pluralism”, with a particular focus on the manner in which chosen research methods have informed these efforts at theoretical triangulation. Design/methodology/approach – The authors conduct an analysis of how to employ theoretical triangulations and methodological pluralism in accounting and organizational research. To this end, they use prior empirical evidence for illustrative purposes. Findings – The authors argue that using theories with epistemological tensions that are captured by appropriate research methods enable one to explore different, sometimes even contradictory, layers of meanings of realities pertaining to management accounting information and processes in organizations and society. Originality/value – The paper contributes to the thinking about the interaction between theory development and research methods chosen by demonstrating how and under what circumstances multiple theories could be meaningfully integrated and executed to provide deeper understandings of accounting and organizational phenomena.
Keywords: Theoretical triangulation; Theoretical pluralism; Multiple theories; Organizational research; Management accounting; Accounting research; Methodological pluralism